First records of the pantropical spotted dolphin Stenella attenuata, within groups of common dolphins Delphinus delphis in northern Peru - Martínez, Lara; Silva, Sebastián; Alcorta, Belén; Pacheco, Aldo S. (Revista de Biología Marina y Oceanografía, 2021)
Although dolphins are mostly known to form single species groups of varying size, occasionally they aggregate in mixed-species groups. The presence of mixed-species delphinid groups along the Peruvian coast is unknown. Herein, we report the presence of a single pantropical spotted dolphin (Stenella attenuata) within large groups of the common dolphin (Delphinus delphis) at Los Organos in the northern coast of Peru. Sightings occurred on October 10th, 2016, January 7th, 2018 and September 21st, 2019. In one sighting the mixed group was feeding, while during the other two sightings the group was travelling. These records add new evidence about mixed-species delphinid groups in coastal waters of Peru.